Carbon Nitride Thin Film‐Sensitized Graphene Field‐Effect Transistor: A Visible‐Blind Ultraviolet Photodetector. Issue 16 (27th April 2022) - Palanisamy, Tamilarasan; Mitra, Somak; Batra, Nitinkumar; Smajic, Jasmin; Emwas, Abdul‐Hamid; Roqan, Iman; Costa, Pedro M. F. J.
Abstract: Ultraviolet (UV) photodetectors often suffer from the lack of spectral selectivity due to strong interference from visible light. In this study, the exceptional electrical properties of graphene and the unique optical properties of carbon nitride thin films (CNTFs) are used to design visible‐blind UV photodetectors. First, polycrystalline CNTFs with different thicknesses (12–94 nm) are produced by thermal vapor condensation. Compared to the bulk carbon nitride powder, these films have a considerable sp 2 nitrogen deficiency, which is thickness dependent. In addition to showing a wider bandgap than the bulk counterpart, their optical absorption profile (in the ultraviolet–visible range) is unique. Critically, the absorbance falls sharply above 400 nm, making the CNTFs suitable for ultraviolet photodetection. As a result, graphene field‐effect transistors (GFETs) sensitized with CNTFs show 10 3 A W −1 responsivity to UV radiation, a stark contrast to the negligible value obtained in the visible spectrum. The effect of film thickness on the photoresponse is determined, with the thinner CNTF leading to much better device performance. The CNTF/GFET photodetectors are also characterized by their fast response and recovery times, 0.5 and 2.0 s, respectively. These findings pave a simple route for the development of sensitive, visible‐blind UV photodetectors. Abstract : Carbon nitride thin films (CNTFs) of various thicknesses are deposited by thermal vapor condensation and transferred by water‐assisted method. The visible‐blind ultraviolet (UV) photodetector, fabricated by sensitizing graphene field effect transistors with CNTFs, shows 10 3 A W −1 responsivity to UV radiation at a switching and visible light rejection ratio of 157 and 48.2, respectively.